Assessment of non consumptive wildlife oriented tourism in Sukau, Sabah using travel cost method - Muhamad Ali, Abdul Hamid; Mohammad Afandi, Syamsul Herman; Emmy, Prisca Jemie; Shuib, Ahmad; Ramachandran, Sridar; Samdin, Zaiton (Universiti Malaysia Sarawak, 2018)
This study focuses on valuing the Wildlife River Cruising (WRC) activity in a rural area located in Kinabatangan River, Sabah. The Kinabatangan River (KR) is rich with natural biodiversity resources and is one of the main attractions for tourism in Sabah, Malaysia. The objective of this study is to determine the characteristics of tourists’ participation in WRC, in terms of their socio-demographic backgrounds, and to estimate the economic value of WRC activity in Sukau, Sabah. An on-site questionnaire was used to obtain primary data for this study. The questionnaire used for the on-site survey was designed to capture the socio-economic demand of WRC and to estimate the economic value of WRC activity. The findings illustrate the value estimated per visit, per person was RM3.20 and the total estimated recreational value of WRC was RM40,149.63 for the year 2014. The data collected was vital for various local stakeholders, especially the Sabah State Government and tourism agencies, to value the area as a crucial and valuable natural resource to preserve. This can possibly initiate the potential and development of economic growth in the area, which could also improve the livelihoods of the local community.